Posteromedial Approach for Fixation of Posterior Fragment in Complex Tibial Pilon Fracture: Posteromedial Approach for Fixation of Posterior Fragment in Complex Tibial Pilon Fracture - Martins, Carla; Varzielas, Miguel; Morais, João; Mendes, Eduardo (Gazeta Médica, 2018)
Fractures of the posterior malleolus are common in ankle fractures. Its fixation is important for syndesmotic stability and plays an important role in the prevention of post-traumatic arthrosis and, consequently, leads to a better functional outcome. Reduction quality is best if you use a backtrack compared to usual techniques. We report the case of a 52-year-old male with a tibial pilon fracture AO/OTA 43C3 and Bartonicek type 3. The anatomical reduction and fixation of the posterior malleolus was performed through a posteromedial approach, with good functional results 9 months postoperatively. The posteromedial approach is a safe way to reduce and fix the posterior malleolus, which also allows the reduction and fixation of the remaining distal tibia, allowing a rapid functional recovery and minimizing late degenerative complications.